Orbital myiasis - Pierre-Filho, Paulo de Tarso Ponte; Pierre, Érica Teles Linhares; Pierre, Leandro Mont´Alvene (Revista de Ciências Médicas, 2006)
lnvasion of the orbit by dipterous fly larvae, an uncommon form of myiasis, may result in sequelae ranging from minar irritation to blindness, and even death. We report a case of a 55-year-old man with destructive orbital myiasis resulting in complete loss of the ocular globe. He presented with severe pain and swelling in his orbital region. Larvae were seen and identified as Cochliomyia hominivorax. Oral ivermectin and intravenous antibiotic were administered prior to surgery. Although infrequent, orbital myiasis may be severe enough to require evisceration or exenteration.